Analysis Two Dimension Heat Conduction in Functionally Graded Materials Using Finite Element Methods - Rezza Ruzuqi (International Journal of Science and Society, 2020)
Along with the progress of the industrial world, both the aviation industry, the health industry, the chemical industry, the electronics industry, and so on, the need for composite materials is increasing to meet market demand. Functionally Graded Materials (FGMs) are an advanced material class of composite materials that have material properties that vary from one point to another. In this study, two-dimensional heat conduction analysis will be conducted in FGM using the Finite Element Method (FEM). Three models gradation FGMs properties examined in the study, namely polynomial, Trigonometry, and Exponential. The response temperature of FGMs using gradation three models compared and analyzed. The optimum temperature distribution of four models built with the ANSYS software. The result is that heat conduction in trigonometric variations is very good, resulting in low-temperature values when compared to both of them. Then, the performance and efficiency obtained using FEM to analyze two-dimensional heat conductivity in FGMs is also very good.